Company law and corporate governance in Malaysia- harmonisation of Shariah and the common law - Mohd. Sulaiman, Aiman @ Nariman; Rachagan, Shanthy (Routledge, Taylor & Francis, 2017)
The last two decades have seen prolific company law reform and corporate governance transformation internationally. The changes have been attributed to various factors ranging from changes to shareholding demographics, the growth and impact of technology on corporate law and practice to new business and investment models. An added dimension to corporate law and governance reform is the growth of Islamic capital market and the Islamic financial services industry. This development has intensified interest about Shariah or Islamic principles in commerce particularly its interaction with conventional company law and practice.